ANALISIS YURIDIS PENGGUNAAN KTP DALAM PEMBERIAN BANTUAN SOSIAL MENURUT PERATURAN PERUNDANG – UNDANGAN YANG BERLAKU - Naila Nursyavika; Rangga Aldiansyah; Yolanda; Maulina Fadhilah (PT. Hasba Edukasi Mandiri, 2025)
The National Identity Card (KTP), as a legal identity document, is a crucial instrument for data collection and distribution of social assistance (bansos) in Indonesia. The use of the KTP serves as the basis for verifying beneficiaries in accordance with population administration regulations. This study aims to analyze the legal basis for using the KTP in providing social assistance based on applicable laws and regulations, including the Population Administration Law, the Law on Handling the Poor, and regulations related to the Integrated Social Welfare Data (DTKS). The research method used is normative juridical, with a regulatory and contextual approach. The results indicate that the KTP is not the sole requirement for receiving social assistance, but it is a mandatory document to ensure the validity and accuracy of population data. The distribution of social assistance must refer to the DTKS and the National Identification Number (NIK) as the key to data integration.